A phase I clinical trial of thymidine kinase-based gene therapy in advanced hepatocellular carcinoma - Sangro, B. (2010)
The aim of this phase I clinical trial was to assess the feasibility and safety of intratumoral administration of a first-generation adenoviral vector encoding herpes simplex virus thymidine kinase (HSV-TK) gene (Ad.TK) followed by systemic ganciclovir to patients with advanced hepatocellular carcinoma (HCC). Secondarily, we have analyzed its antitumor effect. Ten patients were enrolled in five dose-level cohorts that received from 10 10 to 2 × 10 12 viral particles (vp). Ad.TK was injected intratumorally and patients received up to three doses at 30-day intervals. Positron emission tomography was used to monitor TK gene expression. Ad.TK injection was feasible in 100% of cases. Treatment was well tolerated and dose-limiting toxicity was not achieved. Cumulative toxicity was not observed. Hepatic toxicity was absent even in cirrhotic patients. Fever, flu-like syndrome, pain at the injection site and pancytopenia were the most common side effects. No partial responses were observed and 60% of patients showed tumor stabilization of the injected lesion. Importantly, two patients who received the highest dose showed signs of intratumoral necrosis by imaging procedures. One of them achieved a sustained stabilization and survived for 26 months. In conclusion, Ad.TK can be safely administered by intratumoral injection to patients with HCC up to 2 × 10 12 vp per patient.